Non-stationary discharge patterns in motor cortex under subthalamic nucleus deep brain stimulation - Santaniello, Sabato; Montgomery, Erwin B.; Gale, John T.; Sarma, Sridevi V. (Frontiers in Integrative Neuroscience, 2012)
Deep Brain Stimulation (DBS) of the subthalamic nucleus (STN) directly modulates the basal ganglia, but how such stimulation impacts the cortex upstream is largely unknown. There is evidence of cortical activation in 6-hydroxydopamine-lesioned rats and facilitation of motor evoked potentials in Parkinson’s disease (PD) patients, but the impact of the DBS settings on the cortical activity in normal vs. Parkinsonian conditions is still debated. In recent studies, we used point process models to analyze non-stationary activation patterns and inter-neuronal dependencies in the motor and sensory cortices of awake non-human primates during STN DBS. We reported that these features are enhanced after treatment with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), which causes a consistent PD-like motor impairment, and that high-frequency DBS (i.e., >100 pulses-per-second [pps]) strongly reduces the short-term patterns (3-7ms period) both before and after MPTP treatment, while it elicits a consistent short-latency post-stimulus activation. Low-frequency DBS (≤50pps), instead, had negligible effects on the non-stationary features while decreased the burstiness of the spike trains. We evaluate here the impact of the DBS settings on the cortical discharge patterns by using tools from the information theory (receiver operating characteristic curve, information rate, etc.) and report that the probability of spiking of the cortical neurons is significantly conditioned on the DBS settings, with such dependency being significantly larger for high- vs. low-frequency DBS. Overall, the selective suppression of non-stationary features and the increased modulation of the spike probability suggest that high-frequency STN DBS enhances the neuronal activation in motor and sensory cortices, presumably because of reinforcement mechanisms, which perhaps involve the overlap between feedback antidromic and feed-forward orthodromic responses along the basal ganglia-thalamo-cortical loop.